Assessment of the lysine requirement of healthy young male adults through albumin and IgG in plasma - Tian, Ying; Bao, Yun; Chen, Fang; Meng, Chanfang; Sun, Yi; Zhang, Tao; Ge, Jing (Progress in Nutrition, 2022)
Background and aim: The lysine requirement from the indicator amino acid oxidation (IAAO) method has not been validated with the measurement of health. The aim of the study was to assess the lysine requirement of healthy young male adults from the IAAO technique through the concentrations and the fractional synthesis rates (FSRs) of albumin and IgG in plasma.Methods: Five healthy young men participated in the self-controlled study. The intakes of lysine, weights and body composition, concentrations and FSRs of albumin and IgG in plasma of the subjects were determined both in the free-living, self-selected diets and in the controlled lysine diets (controlled for 10 weeks, lysine intake was equal to the lysine requirement from the IAAO method of 70 mg·kg-1·d-1).Results: Although the intakes of lysine, plasma concentrations of IgG and FSRs of albumin and IgG were all significantly lower in the controlled lysine diets (P0.05).Conclusions: The lysine intake of 70 mg·kg-1·d-1 from the IAAO method was sufficient for the subjects at least within the 10-week study